EXPLORING THE IMPACT OF SOCIOCULTURAL FACTORS ON POSITIONING WOMEN IN MANAGEMENT - Hristić, Daniela B.; Čabrilo, Slađana R.; Savić Šikoparija, Tatjana S. (Poslovna ekonomija, 2017)
Job division according to gender is, in its roots, of social and cultural character. Gender characteristics, cultural heritage and system of values in their living and working environment, have influenced women rather than men, in their professional development and progress within leadership hierarchy in organizations. This study is focused on a problem of women’s professional promotion. The basic assumption is that positioning a woman in managerial structure of an organization, is influenced by a group of sociocultural factors such as social background, residential location, level of education and close environment which defines individual’s action, recognition, understanding and evaluation of information, motives and achievements. These bundle of sociocultural factors have been referred to as an individual cultural capital. The main aim is to identify and analyze supportive and non-supportive factors, within the set of explored sociocultural factors, a woman faces on her way up the managerial hierarchy as well as to find possibilities to manage relevant factors in order to enable the woman to fully realize her professional potential and reach the highest possible level at managerial hierarchy. The findings prove relevance of explored factors and their influence on woman’s professional promotion.